FORMULASI TEPUNG PENYALUT BERBASIS TEPUNG JAGUNG DAN PENENTUAN UMUR SIMPANNYA DENGAN PENDEKATAN KADAR AIR KRITIS [Formulation of Corn Flour-Based Batter and Prediction of Its Shelf Life using Critical Moisture Approach] - . Sugiyono; . Fransisca; Aton Yulianto (Jurnal Teknologi dan Industri Pangan, 2010)
The objectives of this study were to obtain the best formula for corn flour-based batter and to predict its shelf life using critical moisture approach.  According to a hedonic test, the best batter formula was composed of 60% corn flour, 12.5% rice flour, 12.5% tapioca starch, and 15% glutinous rice flour. Addition of glutinous rice flour in the formula changed the proportion of amylose and amylopectin in the batter. As a result, the retrogradation of the batter decreased and the texture of its fried product was preferred. A critical moisture approach was used to predict the shelf life of the batter. The critical moisture content of the batter was 0.16 g H2O/g solid.The isotherm sorption phenomenon of the batter was best described using Hasley model. The shelf life of the product was 7 months when packaged in polypropylene (0,07 g/m2day.mmHg) at 85% RH.